Changes in Revealed Comparative Advantage of South Korea and her Major European Union Trading Countries - Gi Seung, Kim; Jin, Kim Seung (WILAYAH: The International Journal of East Asian Studies, 2014)
This paper analyzed how revealed comparative advantage (RCA) of South Korea and her major EU trading countries (i.e., France, Germany, Italy, Spain, and UK; FGISU in short hereafter) in the manufacturing sector changed over time for the period of 2000-2010 by using OECD International Trade by Commodity Statistics. In order to find major determinants of RCA of South Korea and FGISU, the correlations coefficients and multiple regression analyses were utilized. It was found that South Korea exported products which are less skilled human capital intensive and more R&D intensive for the entire period. France is found to have exported products which are more physical capital intensive and more R&D intensive for most of the period. It was found that Germany exported products which are more skilled human capital intensive for most of the period. Italy is also found to have exported products which are less physical (and skilled human) capital intensive and less R&D intensive for the entire period. It was found that Spain exported products which are less R&D intensive for the entire period. UK is also found to have exported products which are more physical (and skilled human) capital intensive and more R&D intensive for the entire period. Therefore both South Korea and FGISU should try to export more of these products to the world market from now on.